Puritanism, Spiritual Kinship, and the Lord's Supper in Elizabethan and early Stuart England - Baddley, Jonathan (Church history, 2024)
The rhetoric of spiritual kinship was a pungent part of a "discourse of separation" which materialized among the English puritans in post-Reformation England. Using print literature aimed at properly preparing the godly to come "worthily" to the Lord's Supper, most of which was penned by puritan divines, this article examines family language in use among the godly in the context of the communion meal in the Elizabethan and early Stuart national church. This rhetoric signaled a real identity - an identity tied intimately to the nexus of right doctrine and a certain type of English Protestant practice. The present essay traces out the theological framework that buttressed this identity and suggests the ways in which family language fostered both inclusive and exclusive responses among the godly as they sought to "rightly" celebrate the sacrament. It argues that the use of the language of spiritual kinship helped the godly come to terms with their uncomfortable position in a national church they considered insufficiently reformed, and with the difficulties that ensued from "holy" living, as naturally unholy beings, in a fallen world. This study contributes to our understanding of the informal mechanisms by which early modern English Protestants could navigate the choppy waters of social and religious life in Elizabethan and early Stuart England. More generally, this consideration of a distinctive puritan usage of familiar scriptural language to make sense of England's religious landscape in this period underscores the interpretive importance of remaining acutely aware of discursive context in early modern religious sources.